FAKTOR-FAKTOR YANG MENYEBABKAN ANAK TIDAK MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI TAHUN 2018 DI KECAMATAN KUOK KABUPATEN KAMPAR - Lena Lena; Zahirman Zahirman; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research was motivated by many children who did not continue their tertiary education in Kuok District, Kampar Regency. It is affected by both internal factors and external factors. The internal factors are such as physical, psychological, and fatigue. And the external factors are such as family, school, and community. The formulation of the problem in this study is "What are the factors which caused the students do not want to continue their study to the university level to 2018 in Kuok District, Kampar Regency?" This study aims to determine the factors which caused the children not to continue to higher education in Kuok District, Kampar Regency. This research was conducted in Kuok District, Kampar Regency. Conducted from February to March. This research use descriptive qualitative approach. Data collection techniques used are observation, interviews, and documentation. As the result of this study it was proven that there are still many children who did not continue their tertiary education in Kuok District, Kampar Regency dominated by family factors are family economic conditions.Key Words: Factors, Education, Higher Education